A (re)significação do ensino a partir da formação continuada de professores nos anos finais do ensino fundamental - Chaves, Ivanilda Cabral Da Costa (2022)
The general objective of this research is understanding and analyzing the mechanisms of (re)signification of pedagogical practice of Elementary School II teachers, from the public education network of Alfenas (MG), those who participate in processes of continuing teacher training. The text was based on theoretical references, according to the postulates of Pimenta (2012); Benachio (2011); Lima (2010); Tardif (2014); Formosinho and Araújo (2011); Libâneo (2004); Day (2001); Nóvoa (1999, 2003 and 2017); Garcia (1999); Imbernón (2009, 2010 and 2011); Nazar (2016); Araújo (2009); Freire (1996) and Demo (2009). The data gathering was divided into two stages, the first consisted of the application of a structured questionnaire, with 22 teachers. From this group, three semi-structured interviews were validated for inferences and discussions. When approaching the continuing teacher training, following the initial one, one believes that it is a need that is presented by professional activity itself, which goes beyond participation in courses, qualifications, training, lectures and sporadic seminars. It was possible to identify, both in the questionnaire and in the interviews, that the continuing training programs and activities developed by the schools and SEME, are identified as modules, in addition to the activities provided by the partner institutions. Through the interviews, we realized that it is possible to (re)signify pedagogical practices in elementary school II, plus there is also a need to seek other training further those offered by schools, SEME or other agencies/institutions. Concluding this object of study, we hope this research may contribute to the daily life of the oficial spaces of Brazilian education, so there may be a new look at the continuing teacher-training education and then be able to promote an improvement of teaching work and of its pedagogical practice, (re)signifying it and creating favorable conditions for the transformation to take place.